Acute effects of unilateral conditioning activity on unilateral and bilateral jumping performance and bilateral strength asymmetry - Jonatan Helbin; Agata Latocha; Michał Spieszny; Paulina Ewertowska; Michał Wilk; Michał Krzysztofik (Scientific Reports)
Abstract The majority of motor tasks in sports are executed unilaterally, however research on the impact of unilateral conditioning activities (CAs) on both unilateral and bilateral sports tasks remains limited. Therefore, the aim of this study was to evaluate the effects of isometric and plyometric unilateral CAs on unilateral and bilateral jumping performance. The study involved fifteen resistance-trained males who participated in three experimental sessions: 3 sets of 3 s of maximum isometric single-leg quarter-squats or 3 sets of 5 single-leg tuck jumps as CAs, along with a control condition without CA. Measurements of single-leg jump (SLJ) and countermovement jump (CMJ) were taken 5 min before, and at approximately the 3th, 6th and 9th minute after the CA. The analysis did not show any statistically significant interactions nor a main effect of condition or time (p > 0.05) for CMJ height and relative peak power. However, a main effect of time (p = 0.02) to increase non-dominant SLJ height from baseline to best post-CA time-point was found (+ 0.8 ± 2.5 cm; Cohen’s d = 0.22). Neither isometric nor plyometric CAs significantly affected CMJ and SLJ performance. The observed increase in jump height for the non-dominant leg is likely due to motor learning rather than the effects of the applied CAs.